0 - Editorial: by Godwin Murunga & Divine Fuh - system, journal (CODESRIA Bulletin, 2021)
This edition of the Bulletin is published on the backdrop of celebrations marking the birth of the Council. This year, CODESRIA turned forty-five, a remarkable achievement for an organisation that started in the 1960s as the Council of Directors of Economic and Social Research Institutes in Africa. In 1973, it was formally established as an independent panAfrican research organisation with Samir Amin as first Executive Secretary. February has therefore become a special month for the Council. The founding of CODESRIA was apart a response to a history of epistemic violence and colonial hegemony that continued to define research and critical thinking in and about Africa. The Council was also born out of the need for intellectual hegemony to accompany the new wave of independence and self-rule that swept across the continent in the 1960s and 1970s. Formally established outside the climax of anticolonial and independence struggles, sixteen years after Ghana achieved independence in 1957, CODESRIA grew in an international knowledge system to which it had to relate, but against which it had to define an autonomous agenda. It is not surprising that amongst many debates, endogenising knowledge from the continent and radically ‘de-linking’ Africa from the falsehoods of abstract Eurocentric intellectualism was a priority. The Council priorities were achieved through promoting vigorous research, networking and publishing on African realities. With an emphasis on publishing by Africans, the Council deliberately privileged strategies to decolonise knowledge and deal with resilient epistemic violence. Forty-five years after, as the international knowledge system mutates and becomes more invidious, this mission has acquired greater relevance and becomes more pressing as it was during CODESRIA’s founding. This historical context explains why CODESRIA Day is special. Until recently, the Council has observed February 1st to celebrate its birthday by hosting an event held at its headquarters in Dakar, Senegal. In 2018, however, CODESRIA inaugurated the CODESRIA Day Lecture as an Annual Lecture Series to commemorate the day. On February 21st with Sabelo J. Ndlovu-Gatsheni presented the inaugural CODESRIA Day Lecture titled ‘The Struggles for Epistemic Freedoms in Africa’ in Harare, Zimbabwe during the Meaning-Making Research Initiative (MRI) launch workshop. We publish an abridged version in this issue of the bulletin. This edition of the Bulletin thus critically engages resurgent debates around epistemic violence, these debates are apt because they touch on an issue that is core to the CODESRIA mandate. Other than Sabelo J. Ndlovu-Gatsheni’s exposé on struggles for epistemic freedom in Africa, the Bulletin carries a thought- provoking piece by Francis Nyamnjoh that (re) situates and (re)imagines contemporary sociological knowledge in the South African context against a background of struggles for epistemic freedom. This is symbolised by the “Rhodes Must Fall”, “Fees Must Fall” and related movements. Perhaps even more provocative is Tafadzwa Tivaringe counterpoise that argues that race-centric efforts to decolonize the academy run into the inevitable pitfall of biological essentialism in a manner that is inadvertently antithetical to the emancipation of already subjugated epistemologies. The next set of articles revisit the discussion on Africa’s uncomfortable relationship with intellectuals on the one hand and African Studies on the other hand. Issa Shivji responds to Edward Said’s (1994) question whether all organic intellectuals are public intellectuals and vice versa, emphasising that all public intellectuals are not organic intellectuals, especially as many public intellectuals give up their organic link with the oppressed masses in order to avoid tarnishing their public image. Livio Sansone discusses the decolonisation of African Studies, explaining how to overcome the colonial division of labor between producers of academic knowledge in the Global North and suppliers of information in the Global South. Ayanda Manqoyi and Mirjam de Bruijn’s contributions reflect on the mobility of African scholars. Manqoyi focuses on South African exceptionalism and parochialism, and its subsequent devaluation of African knowledge and intellectuals. de Bruijn mobilises the notion of ‘access denied’ to reflect on Europe’s visa policies and how this has dealt fatal blows to the dreams of young Africans seeking to expand their aspirational nodes. The next two articles engage with concerns around bodily identities with Bebel Nepomuceno using the ascension of Hip-Hop identity movement among Brazil’s Black youth to discuss the use of Black aesthetics as a way of confronting hegemonic power while Zoly Rakotoniera addresses the production and marking of queer bodies in Malagasy through humour. This is followed by a group of three articles by Dennis Masaka, Mlamuli Hlatshwayo and Kehdinga George Fomunyam, Donkor et al., Paola Vargas Arana, and Muhammed Bolaji are focused on changing higher education dynamics in Africa. The Bulletin concludes with two articles on African cinema with Africanus Aveh reflecting on the complexities of production in Ghana’s film industry, while Okello Oculi closes with a freestyle discussion on Ousmane Sembene and his engagement with masculinity and femininity in film. The Council hopes you will find the Bulletin refreshing and provocative and that you will indicate this by engaing the ideas contained in the Bulletin. We invite reactions, responses and rebuttals and hope this discussion will go beyond the Bulletin to other forums and platforms. Godwin Murunga Executive Secretary, CODESRIA and Divine Fuh Head of Publications and Dissemination, CODESRIA